Consideraciones para la caracterización empresarial del constructor informal (2010)
This work is based on monitoring the reference literature production and tries to emphasize the characterization of the builder informal business, particularly the so-called “Auto construction”, although by implication, other forms of urban production. The document seeks to identify elements of land management and informal financial support, to potentially support the integral government of the formal construction company.